Accelerated Manufacturing Processes And Their Role In Enhancing The Intrinsic Capabilities Of The Company - Jabbar Jodah, Shaymaa; Ali Abdulameer, Safaa Abid; Saadoon Salman, Safaa (Opción, 2019)
The current study aims at specifying the role of accelerated manufacturing processes in enhancing the intrinsic capabilities by applying them in the Iraqi organizations. The study has started with certain questions; these questions are considered as the problem of this study. Answering these ques- tions lead to understand the relationship and the effect between the variables of the study. To be more specific, this study introduces two main hypotheses and from them a group of sub hypotheses are created. The practical side of this study is tested in the company of Noor Al- Kafeel for animal and food products. The study is applied on a sample of employees constitutes of (40) employer in the intended company. They were distributed according to several administrative levels in the different sections of the company. In this study, the researcher used the questionnaire as a main tool to collect the required infor- mation, in addition to the personal interviews. To fulfil the aim of this study, the researcher depends on the main and sub hypotheses which reflect the rela- tionship between accelerated manufacturing processes and the intrinsic capa- bilities. These hypotheses were tested between variables by using correlation coefficient (Spearman), and (T) test to illustrate/ understand the meaning of the relationship between variables, and (F) test to determine the significance of the regression equation. Moreover, (R2) is used to explain the amount of the effect of the independent variable on the dependent variable.